UNDERSTANDING CONSUMER BEHAVIOUR IN A DIGITAL AGE - Olimpia Elena Mihaela OANCEA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2023)
Consumers are changing the ways they use digital platforms at lightning speed. To benefit, companies must take a refined look below the surface to understand who is doing what. In recent decades, the Internet, evolving technologies, and social media have led to the evolution of consumer behaviour. The changes in customer behaviour driven by digital developments provide many opportunities and challenges that businesses also need to deal with online. The better companies know about the behaviour of their customers, the easier they can engage with them using different strategies marketing. In this article, I will explore the concept of consumer behaviour, examine how it has changed in the digital era, and discuss strategies for businesses to align themselves with these shifting trends.